Digital imaging for cultural heritage preservation : analysis, restoration, and reconstruction of ancient artworks - Stanco, Filippo; Battiato, Sebastiano; Gallo, Giovanni, 1962- (Boca Raton, FL : CRC Press, 2011)
"This edition presents the most prominent topics and applications of digital image processing, analysis, and computer graphics in the field of cultural heritage preservation. The text assumes prior knowledge of digital image processing and computer graphics fundamentals. Each chapter contains a table of contents, illustrations, and figures that elucidate the presented concepts in detail, as well as a chapter summary and a bibliography for further reading. Well-known experts cover a wide range of topics and related applications, including spectral imaging, automated restoration, computational reconstruction, digital reproduction, and 3D models"--Provided by publisher.
"Preface Paintings, frescos, antique photographic prints, incunabulas, old books, handwritten documents, sculptures, ceramic fragments and other ancient manufacts constitute the elements of an extremely valuable and immense historical patrimony. Their digitalization opens up the possibility to use various image processing and analysis and Computer Graphics techniques to preserve this Cultural Heritage for future generations. Digital imaging solutions can be used to generate virtually restored versions of the original artworks to be presented in online museums and/or for further development of historical studies. Application of various feature extraction and image data analysis techniques is useful to address problems of authorship and artwork style categorization in the history of arts. Three-dimensional reconstruction of ancient artworks or entire archeological sites allows the creation of multidimensional models that incorporate information coming from excavations, archaeological knowhow and heterogeneous historical sources. Pioneer work in this area has sprung from the close, but too often occasional, cooperation of scientists with historians and archaeologists"--Provided by publisher.
Bibliografske bilješke iza svakog poglavlja. Kazalo.
Keywords: Kulturna baština - Zaštita; Digitalizacija